2019
DOI: 10.3390/w11040850
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Modeling Approach Using Radar-Rainfall Ensemble and Multi-Runoff-Model Blending Technique

Abstract: The purpose of this study is to reduce the uncertainty in the generation of rainfall data and runoff simulations. We propose a blending technique using a rainfall ensemble and runoff simulation. To create rainfall ensembles, the probabilistic perturbation method was added to the deterministic raw radar rainfall data. Then, we used three rainfall-runoff models that use rainfall ensembles as input data to perform a runoff analysis: The tank model, storage function model, and streamflow synthesis and reservoir re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…Comparing the mean Dm with other studies, results show that the mean raindrop diameter in the Philippines for the wet season (at 1-min Δt) is the same as the value observed by Tokay and Short (1996) for the tropical ocean (1.41 mm). However, the mean Dm in this study is observed to be lower than the study by Lam et al (2015) in Malaysia (1.74 mm), and from the results of Chen et al (2013) in Eastern China (1.66 mm), but is observably higher than that from the study of Lee et al (2019) in Northern Taiwan (1.16 mm), from the study by Seela et al (2017) in Palau (1.11 mm) and from 1-min DSD results in Taiwan from the same study (1.24 mm). These results imply that raindrops in the Southern Luzon, Philippines is generally smaller than that from Malaysia and Eastern China but are larger than those from Taiwan and Palau.…”
Section: Drop Size Distribution and Normalized Gamma Parameterscontrasting
confidence: 86%
See 3 more Smart Citations
“…Comparing the mean Dm with other studies, results show that the mean raindrop diameter in the Philippines for the wet season (at 1-min Δt) is the same as the value observed by Tokay and Short (1996) for the tropical ocean (1.41 mm). However, the mean Dm in this study is observed to be lower than the study by Lam et al (2015) in Malaysia (1.74 mm), and from the results of Chen et al (2013) in Eastern China (1.66 mm), but is observably higher than that from the study of Lee et al (2019) in Northern Taiwan (1.16 mm), from the study by Seela et al (2017) in Palau (1.11 mm) and from 1-min DSD results in Taiwan from the same study (1.24 mm). These results imply that raindrops in the Southern Luzon, Philippines is generally smaller than that from Malaysia and Eastern China but are larger than those from Taiwan and Palau.…”
Section: Drop Size Distribution and Normalized Gamma Parameterscontrasting
confidence: 86%
“…However, a reason for such high distribution might be the presence of outlying number of drops on larger diameters that affects the value of µ. Moreover, the average µ value for 1-min data for the wet season (µ = 11.20) is also significantly higher than the µ values of China (µ = 3.51, 1-min Δt), Palau (µ = 8.37, 1-min Δt), Taiwan (µ = 6.72 and 5.60 for 1-min and 10-min Δt, respectively), and Malaysia (µ = 6.76, 1-min Δt) (Chen et al 2013;Lam et al 2015;Lee et al 2019;Seela et al 2017). However, when using longer time-steps (> 1-min), the values of µ appears to be closer to the aforementioned areas of comparison, albeit still a little higher in magnitude.…”
Section: Drop Size Distribution and Normalized Gamma Parametersmentioning
confidence: 73%
See 2 more Smart Citations
“…Using this dataset, computing MAP explicitly considers the spatial variability of rainfall compared with ground-based gauge rainfall [24]. Some previous studies have tested the performance of different NEXRAD precipitation products against the ground-based gauge data in hydrological modeling, and results have shown the superiority of NEXRAD data because of their ability to capture the rainfall spatial variations for better outcomes [25][26][27]. Only a few studies have attempted to couple NEXRAD Level 3 rainfall with the HEC-HMS model for the assessment of LULC change impact on urban flooding.…”
Section: Introductionmentioning
confidence: 99%